THEORETICAL AND PRACTICAL ASPECTS OF DEVELOPING INSURANCE SERVICES BASED ON DIGITAL TECHNOLOGIES - G‘oziyeva Aziza Abdusalomovna; Tuxtabayev Jamshid Sharafetdinovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article analyzes the theoretical foundations of digitalization in the insurance sector, its economic and institutional significance, as well as the processes of digital transformation being implemented in the insurance market of Uzbekistan. The study examines the economic and legal essence of the concept of insurance based on various scientific sources and provides a comparative analysis of definitions given in national and foreign legislation. In addition, the article highlights the results of the introduction of digital technologies in insurance companies, including the Unified Automated Information System (UAIS), electronic policies, CRM/ERP systems, artificial intelligence, Big Data, and blockchain technologies. The paper also analyzes the main indicators of the insurance market of Uzbekistan for 2022–2024, including the number of insurance organizations, charter capital, the dynamics of brokers and agents, and insurance premiums. The findings show that the digitalization of the insurance sector helps increase the efficiency of insurance companies, reduce fraud, ensure service speed and transparency, and improve customer satisfaction. Furthermore, the article scientifically substantiates the advantages of implementing Big Data, artificial intelligence, and blockchain technologies in the insurance sector, as well as their importance in enhancing the competitiveness of the insurance market. The results of the study serve as a basis for developing practical proposals and recommendations aimed at modernizing the insurance system, improving insurance services in accordance with the requirements of the digital economy, and ensuring the sustainable development of the sector.